Advancing leadership in Australasian emergency medicine: Taking stock and looking ahead. (15th June 2021) - Rixon, Andrew; Wilson, Samuel; Judkins, Simon; Bonning, John; Skinner, Clare; White, Peter
Abstract: Since 2018, the Australasian College for Emergency Medicine has collaborated with the Swinburne University of Technology on a research project to understand and enhance the leadership capacity of emergency physicians, beginning with Australasian Directors of Emergency Medicine (DEMs). Over the last 3 years, this research programme has revealed the complexity of leadership in emergency medicine, illuminating the strengths and limitations of extant research and suggesting promising new directions for emergency medicine leadership and leadership development research. This programme has also shed new light on the knowledge, skills and abilities that DEMs need to develop to catalyse change in the systems where DEMs practice both medicine and leadership. We propose that an approach to leadership development that reflects the diversity of DEMs' leadership challenges and the complexity of leadership in emergency medicine would go a long way to enhancing the sophistication, effectiveness and impact of the leadership in emergency medicine.